How do dinosaurs say merry Christmas? - Yolen, Jane; Teague, Mark (New York : Blue Sky Press, 2012)
Illustrations and rhyming text present some of the different ways a well-behaved dinosaur can celebrate Christmas.
105480
Keywords: Stories in rhyme; Conduct of life -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Christmas stories; Children's stories; Juvenile works